How to establish a successful ex vivo lung perfusion program - Makdisi, George; Wozniak, Thomas C. (Annals of Translational Medicine, 2017)
Donor lung shortage is a major limiting factor in lung transplantation. Multiple methods have been used to expand the number of transplanted lungs. Ex vivo lung perfusion (EVLP) is utilized to accept non-standard lungs and to perfuse them in a physiologic setting in order to assess their suitability for transplantation. As EVLP has gained broader utilization in the armamentarium of the lung transplant process, more centers have identified a need to develop an EVLP program. Here we discuss the steps that are useful in establishing a successful EVLP program. We carefully considered various factors which are important in implantation this technology step by step focusing on liaison, logistics, and organization.